A hybrid pre-processing attenuation correction technique for SPECT imaging - Sayed, Inayatullah Shah; Leeman, Sidney (Al Ain University of Science and Technology, UAE, 2006)
Factor acting against quantitation of radioactivity uptake in Single Photon Emission Computed Tomography (SPECT) is the attenuation (scattering and absorption) of gamma photons in the patient, and a number of approximate correction techniques exist. A hybrid technique dealing with the attenuation problem, which combines some pre-processing attenuation correction methods (arithmetic and geometric–mean approaches) is proposed and investigated. The technique is analyzed in terms of data obtained by 360 degree transaxial scanning of a water filled cylindrical phantom (with Tc-99m solution) containing an insert with hot regions of various sizes and at different interior locations. The reconstructed images are assessed in terms of two sets of measurements: (i) standard deviations of the local count rates in the images of a uniformly hot cylinder; (ii) relative count ratios in the images of hot regions positioned at different places in phantom. The results obtained with the hybrid technique reported here are positive, and the clinical context in which the technique may be expected to be useful is indicated.